Advances in industrial and labor relations - Kaufman, Bruce E.; Lewin, David 1943- (Emerald, 2002)
Continuing to provide forward-thinking industrial relations research, Volume 11 of Advances in Industrial and Labor Relations (AILR) features studies of EEOC and FMCS mediation approaches and effectiveness; union organizing, political effectiveness and internal democracy; the effects of broad-based stock option plans on the performance of unionized and non-union companies; and 21st century prospects for a new baby boom generation, employee-driven corporate governance, and global labour markets. These studies offer a variety of disciplinary perspectives, research designs, and analytic methods, yet they all contain important findings, some quantitative and some qualitative, as well as conclusions about key aspects of contemporary industrial relations.
Continuing to provide forward-thinking industrial relations research, this volume includes studies of EEOC and FMCS mediation approaches and effectiveness; union organizing, political effectiveness and internal democracy; and 21st century prospects for a new baby boom generation.